Reciprocal androgen receptor/interleukin‐6 crosstalk drives oesophageal carcinoma progression and contributes to patient prognosis. Issue 4 (23rd January 2017) - Dong, Hongmei; Xu, Jinjin; Li, Weiwei; Gan, Jinfeng; Lin, Wan; Ke, Jierong; Jiang, Jiali; Du, Liang; Chen, Yuping; Zhong, Xueyun; Zhang, Dianzheng; Yeung, Sai‐Ching Jim; et al.
Abstract: Oesophageal squamous cell carcinoma (ESCC), a leading lethal malignancy of the digestive tract, is characterized by marked gender disparity. Clarifying the roles of the function and regulatory pathway of the androgen receptor (AR) will improve our understanding of oesophageal cancer progression, thereby facilitating the personalized management of ESCC. Here we report evidence to show that AR is a key mediator of inflammatory signals in ESCC cancer progression. High AR expression was associated with poor overall survival in tobacco‐using ESCC patients but not in ESCC patients not using tobacco. A gain and loss of AR function enhanced and repressed ESCC cell growth, respectively, by altering cell cycle progression. In mice bearing human ESCC xenografts, silencing AR expression attenuated tumour growth, whereas AR overexpression promoted tumour growth in mice of different androgen statuses (male, female, and castrated male). Array assays revealed that the inflammatory cytokine interleukin‐6 ( IL6 ) is a prominent AR target gene in ESCC. By directly binding to the IL6 promoter, AR enhances IL6 transcription, and IL6 can in turn activate AR expression, thus forming a reciprocal regulatory circuit to sustain STAT3 oncogenic signalling in ESCC. Moreover, high expression levels of both AR and IL6 in human ESCC predict poor clinical outcome in tobacco users. Together, these data establish that AR promotes ESCC growth and is associated with poor patient prognosis. The discovery of a positive feedback loop between IL6 and AR bridges the knowledge gaps among lifestyle factor‐associated inflammation, gender disparity, and oesophageal carcinoma. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.